Methyl 5-chloro-2-hydroxy-3-(4-methoxyphenyl)-4,6-dimethylbenzoate - Muhammad Adeel; Irshad Ali; Peter Langer; Alexander Villinger (Acta Crystallographica Section E, 2009)
In the title compound, C17H17ClO4, the dihedral angle between the mean planes of the two benzene rings is 65.92 (5)°. The methyl ester group lies within the ring plane [deviations of O atoms from the plane = −0.051 (2) and 0.151 (2) Å] due to an intramolecular O—H...O hydrogen bond. In the crystal, molecules are held together by rather weak non-classical intermolecular C—H...O hydrogen bonds, resulting in dimeric units about inversion centers, forming eight- and ten-membered ring systems as R22(8) and R22(10) motifs.